Analysis of the Island Sustainable Tourism base on Tourist' Perception -A Case Study of Mandeh Island, West Sumatera - Sulis Purwanto; Sukma Yudistira; Retnaningtyas Susanti (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2021)
Archipelago tourism has become a widely popular marine tourism destination for visitors and a tourism trend. Sustainable island tourism, which emphasizes environmental, economic, and socio-cultural impacts, is the basis of tourism growth. This research aim to know about tourists' perceptions of Mandeh archipelago's tourist destinations based on sustainable tourism. Questionnaires and literature research were the approaches used to collect research results. The data was analyzed using descriptive frequency statistics presented in the form of percentages. The results showed that the characteristics of tourists, seen from gender, dominate female tourists by 67 percent, with a very active age between 17-25 years of age, 78 percent. The majority of those who visit Mandeh Island more than once are 69%, 72% with friends, and a group. Overall, the Mandeh Islands' expectations of sustainable tourism growth are strong, but some still have issues related to the quality of the Mandeh tourism region's environment. From this study, it can be seen that environmental measures of sustainable tourism need to be strengthened again. As for having a positive effect on sustainable tourism growth in the tourist destinations of the Mandeh archipelago, the collaboration between tourism stakeholders needs to be increased again